Business strategies for enhancing quality of life in the later years - Moschis, G.; Pettigrew, Simone (Springer, 2011)
As the earth’s population ages, businesses globally need to become more attuned to the needs of older consumers. This chapter emphasizes the importance of understanding the factors that enhance well-being in later life, and suggests strategies that can be adopted by marketers to assist consumers achieve this objective. This emphasis on developing strategies that enhance well-being entails a change in philosophy, involving a more holistic approach to marketing that focuses on both profits and enhancing consumer well-being.